Analisis Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Negeri Sipil (PNS) Dengan Motivasi Sebagai Variabel Intervening - Laviena Octora; Luis Marnisah; Meita Istianda (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study is to analyze the influence of organizational culture and leadership style on the performance of civil servants  in Kalidoni sub-district, Palembang city with motivation as an intervening variable where the sample used is a saturated sample, namely all the population of civil servants in the Kalidoni sub-district working environment, amounting to 56 people as a sample. study. Meanwhile, in managing the data, the SPSS program is used with the path analysis method (path analysis). After analyzing the data, the results obtained are the results of the validity tests X1, X2, Y and Z obtained r table of 0.2656 < corrected item total correlations, from the results of reliability tests X1, X2, Y and Z Cronbach's Alpha values ​​in the range 0.801-0.920 > 0.60 so it can be said to be reliable. In the simultaneous test 29.467 is greater than f table 2.78 and the significance value (Sig.) 0.000 is smaller than 0.05 so it can be concluded that Organizational Culture and Leadership Style have a positive and significant effect on motivation simultaneously. The calculated f value of 16.375 is greater than f table 2.78 and the significance value (Sig.) 0.000 is smaller than 0.05, so it can be concluded that organizational culture, leadership style, and motivation have a positive and significant effect on performance simultaneously. Furthermore, the value of R2 in the first path analysis test is 0.527, indicating that the motivation variable is directly influenced by the organizational culture and leadership style variables, while the remaining (100%-52.7%) or 47.3% is influenced by other variables. With the R2 value in the second path analysis test of 0.491, it shows that the performance variable is directly influenced by organizational culture, leadership style, and motivation variables while the rest (100%-49.1%) or 50.9% is influenced by other variables.